2005
DOI: 10.1590/s1020-49892005000100004
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection in mobile populations: the case of Mexican migrants to the United States

Abstract: Our findings contrast with previous estimates of HIV among labor migrants in the United States that were based on nonprobability samples. Our findings also underline the need for early HIV prevention interventions targeting this population of Mexican migrants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 4 publications
0
22
1
2
Order By: Relevance
“…Despite these statistics, the majority of studies of Latino men have been conducted on men who have sex with men (MSM) [15], thus it is important to investigate prevalence rates among heterosexual Latinos as well. And while few prevalence studies have been conducted among Latino migrant men [14], the few studies that have done biological testing found low prevalence rates despite high rates of HIV/STI risk behavior [17][18][19].…”
Section: Latinos and Hivmentioning
confidence: 99%
“…Despite these statistics, the majority of studies of Latino men have been conducted on men who have sex with men (MSM) [15], thus it is important to investigate prevalence rates among heterosexual Latinos as well. And while few prevalence studies have been conducted among Latino migrant men [14], the few studies that have done biological testing found low prevalence rates despite high rates of HIV/STI risk behavior [17][18][19].…”
Section: Latinos and Hivmentioning
confidence: 99%
“…The prevalence of risk behaviors and STIs across all migration contexts is at odds with the absence of HIV positive cases reported elsewhere for this same sample of MMIs. 12 This contrast underscores the need to identify the factors that may be protecting MMIs from becoming infected with HIV infection in all three geographic contexts. These may include the type of sexual practices, the characteristics of the network of sexual partners, and biological/genetic host characteristics, to name a few.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the HIV screening have been reported elsewhere. 12 The SUMIB survey collects information on a wide array of socio-demographic aspects related to migration between Mexico and the US. Specific questions on demographics, migration background, and socioeconomic factors were selected for this study (Table I).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,12,14 Es un proceso infeccioso con dos fases. La primera ocurre durante la estancia en Estados Unidos, especialmente entre varones que viajan sin sus parejas y que tienen contactos sexuales sin condón con trabajadoras sexuales 11,14 o con otros hombres.…”
unclassified